Tanggung Jawab Hukum Pengembang Properti Yang Dinyatakan Pailit Terhadap Pemenuhan Kewajiban Kepada Konsumen Ditinjau Dari Teori Kepastian Hukum - Evelyn Millechen; Rasji, Rasji (UNES Law Review, 2024)
The need for adequate housing is a mandate of the Constitution. This is what encourages the growth of the house development industry and ready-to-live buildings in Indonesia. However, in its implementation, the community is often faced with the problem of developer companies being declared bankrupt, causing legal uncertainty for consumers. This is what makes researchers interested in examining these legal issues. This research uses normative juridical research with a statutory approach through secondary data searches. The result of this research is that when the developer enters PKPU and is even declared bankrupt, it is the consumers who suffer great losses. Because, if the developer is declared bankrupt and the Deed of Sale and Purchase (AJB) has not yet belonged to the consumer, the consumer's assets will also be confiscated and auctioned, and the consumer does not necessarily get a share of the proceeds from the auction because it is not certain that the results are sufficient to pay off his share. In this case, it can be seen that in bankruptcy cases, consumers are the most vulnerable. In the absence of AJB in addition to being the last creditor, the consumer is not the owner of the land and the land will be auctioned and divided by the separatist creditor. There needs to be an effort from the government to form a specific regulation governing further provisions and the position of creditors in bankruptcy, PPJB, reservation agreements, Pre-Project Selling obligations of developers, as well as sanctions if it is found that the development company has defaulted or broken promises. Because the Bankruptcy Law and GCPL have different solutions from each other, it is necessary to have clearer arrangements between bankruptcy and consumer protection to create legal certainty.